Necrotic epithelial cells in proximal renal tubules of 2(nd) trimester fetuses: is this “acute tubular necrosis”? - Peres, Luiz Cesar (e-Century Publishing Corporation, 2012)
PURPOSE: The aim of this study is to describe the occurrence of necrotic tubular cells in kidneys of non-macerated fetuses. METHODS: Description of histology and immunostaining results using C9 immunostain of proximal tubular epithelium of kidneys from 30 consecutive non-macerated fetuses’ autopsies. RESULTS: the gestational age ranged from 13 to 22 weeks. The mean gestational age was 18.6 weeks; the cause of death was acute chorioamnionitis in 13 cases (43.3%), termination of pregnancy for fetal anomalies in 13 (43.3%) and other causes in 4 (13.3%). Histology of the kidneys revealed vacuolation of proximal tubule epithelial cells (100%), dilatation of tubules (93.4%) and tubular cell necrosis (53.4%). C9 immunostaining was positive in 24 cases (80%) and was seen in all gestational ages. CONCLUSIONS: These results indicate that tubular cell necrosis is not an uncommon finding in the kidneys of 2(nd) trimester fetuses and may represent acute tubular necrosis (ATN). C9 is a helpful marker in confirming this diagnosis. Future studies may further explore this preliminary observation.